SQ3R Techniques with Let's Read Application for Improvement of Reading Comprehension in Low Class Elementary Students - Endang Sri Maruti; Sri Budyartati; Ersita Silviana (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
The purpose of this study was to determine the planning, process, student responses and the obstacles faced in the application of the SQ3R method with illustrated story media in learning reading comprehension for fourth grade elementary school students. This research is a qualitative descriptive study which was conducted in the fourth grade of SDN 03 Baosan Lor, Ponorogo with a total of 31 students. The methods of data collection were observation, interviews, questionnaires, and documentation. Data analysis uses the Milles and Huberman model, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that lesson plans such as syllabus, lesson plans and media are well structured and planned. The learning process creates an effective atmosphere, runs smoothly and pleasantly, students respond to learning with a very positive response, and the obstacles faced are less than optimal time allocation, and there are 2-3 students who have difficulty in following the learning stage because they are still confused and do not understand. pay attention to the teacher during the learning process.